LEGAL REGULATION OF INVESTMENT ACTIVITY IN UKRAINE: DEVELOPMENT PROSPECTS - Netska, Liubov; Podik, Yana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to develop recommendations for improving the legal regulation of investment activities in Ukraine to stimulate economic growth and increase the country’s investment attractiveness. Research methods: the work used a set of methods: general scientific (analysis and synthesis, induction and deduction) - to study the main provisions of the investment legislation of Ukraine; formal and legal - to study the content of norms, special terms and direct conflicts of regulatory legal acts; comparative legal - to identify best practices for improving regulatory mechanisms; systemic and functional - to clarify the relationship between regulatory legal acts regulating investment activities. Results: it was found that the current investment legislation of Ukraine contains a number of gaps in the legal protection of investors, an overly complex mechanism of state regulation, and the presence of a number of risks for attracting investments; at the same time, positive trends are observed in the adaptation of norms to European standards, the growth of foreign direct investment, and the renewal of approaches to public-private (public-private) partnership; based on a comparative analysis, measures were proposed to improve the regulatory framework, aimed at simplifying procedures, strengthening guarantees of investor rights, and creating a more attractive investment environment. Discussion: the discussion highlights the importance of further harmonization of Ukrainian legislation with European norms; at the same time, the potential of measures to simplify procedures, optimize tax incentives, and strengthen institutional support for investors is discussed, which can become the basis for economic growth and competitiveness of the country.